PENDAMPINGAN PENERAPAN CARA PRODUKSI PANGAN YANG BAIK (CPPB) PADA PRODUKSI KERUPUK RAMBAK TAPIOKA DI UD MEKAR KOTA SEMARANG - Zulhaq Dahri Siqhny; Sri Budi Wahjuningsih; Dian Indudewi; Amerti Irvin Widowati (Jurnal Abdimas Bina Bangsa, 2023)
This community service method includes discussion and observation, formulating recommendations, and socialization along with assistance in implementing good food production methods (CPPB) at UD Mekar which produces tapioca rambak crackers. The data collected includes understanding and application of CPPB in various aspects of cracker production, including raw material selection, processing, sanitation, and product labeling. The results of this service show that UD Mekar has a limited understanding of CPPB. These findings indicate the importance of increasing awareness and education about CPPB at UD Mekar. The implementation of CPPB in cracker production by UD Mekar still has many challenges. However, with increased awareness, training and proper support, UD Mekar can improve product quality and safety. Apart from that, the recommendation for implementing CPPB at UD Mekar can be a reference for future improvements so that food safety for consumers is guaranteed and can improve the quality of tapioca rambak cracker products.